Substitusi Modifikasi Pati Biji Nangka dan Bekatul terhadap Serat Pangan dan Aktivitas Antioksidan pada Mie Kering - Salsabila, Addila; Kurnia, Pramudya; Purwani, Eni (Universitas Tadulako, 2025)
This study aims to evaluate the effect of substituting composite flour made from modified jackfruit seed starch and rice bran flour on the dietary fiber content and antioxidant activity of dried noodle products. Jackfruit seed starch was modified using the autoclaving-cooling method, a physical technique designed to enhance the functional properties of starch, such as thermal stability, resistance to digestion, and increased resistant starch content. On the other hand, rice bran flour was utilized as a source of insoluble fiber and bioactive compounds such as γ-oryzanol and phenolic acids, which are known for their antioxidant properties. The two ingredients were combined in a 1:1 ratio to produce composite flour, which was then substituted into the noodle formulation at levels of 5%, 10%, and 15% of the total flour used. The final noodle products were analyzed for insoluble, soluble, and total dietary fiber content using a multi-enzyme method, as well as antioxidant activity using the DPPH assay. The results indicated a significant increase (p<0.05) in dietary fiber content and antioxidant activity with higher substitution levels. The 15% substitution treatment yielded the best results, with total dietary fiber content of 6.86% and antioxidant activity of 33.70%. This study demonstrates that the combination of modified jackfruit seed starch and rice bran flour holds great potential as a sustainable and nutritious functional ingredient in healthier dried noodle formulations.